Collaborative Equilibrium Coupling of Catalytic DNA Nanostructures Enables Programmable Detection of SARS‐CoV‐2 (Adv. Sci. 18/2021). Issue 18 (22nd September 2021) - Chen, Yuan; Sundah, Noah R.; Ho, Nicholas R. Y.; Natalia, Auginia; Liu, Yu; Miow, Qing Hao; Wang, Yu; Beh, Darius L. L.; Chew, Ka Lip; Chan, Douglas; Tambyah, Paul A.; Ong, Catherine W. M.; et al.
Abstract : Programmable Detection of SARS‐CoV‐2 In article number 2101155, Huilin Shao and co‐workers report the collaborative coupling of enzyme–DNA nanostructures to establish multi‐enzyme catalysis. Through programmable nanostructures and favorable equilibrium architecture, the technology achieves direct and sensitive detection of SARS‐CoV‐2 RNA in native patient samples, within 30 minutes at room temperature.